LDL triglycerides, hepatic lipase activity, and coronary artery disease: An epidemiologic and Mendelian randomization study - Silbernagel, Günther (Atherosclerosis, 2018)
BACKGROUND AND AIMS: High concentrations of low density lipoprotein (LDL) triglycerides have been associated with prevalent angiographic coronary artery disease. The present analysis was designed to investigate the association of LDL triglycerides with cardiovascular mortality and to explore possible mechanisms that may link LDL triglycerides to cardiovascular risk. METHODS: LDL triglycerides were measured in 3,140 participants of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. They were prospectively followed for cardiovascular mortality (median duration 9.9 years). Genome wide association data for LDL triglycerides were available for 2,900 LURIC participants. Genetic data and measurements of hepatic lipase activity were available for 478 participants of the HERITAGE Family study. Genome wide association data for cardiovascular disease were available for 184,305 participants of the CARDIoGRAMplusC4D consortium. RESULTS: There was a continuous positive association between LDL triglycerides and cardiovascular mortality (hazard ratio for 5(th) vs. 1(st) quintile = 2.53, p < 0.001) and this association was similar in males and females. Genome wide association analysis in LURIC revealed that LDL triglycerides were strongly associated with variation in the hepatic lipase region (p < 10(−15) for rs1800588 and rs10468017). The LDL triglyceride raising alleles in rs1800588 and rs10468017 were associated with low hepatic lipase activity in HERITAGE and increased cardiovascular risk in CARDIoGRAMplusC4D. Two-sample Mendelian randomization analysis (HERITAGE and CARDIoGRAMplusC4D) using rs1800588 and rs10468017 as instrumental variable suggested that low hepatic lipase activity may cause increased cardiovascular risk (p = 0.013). CONCLUSIONS: Low hepatic lipase activity may link high LDL triglycerides to increased cardiovascular risk.